Benda Terdaftar dalam Konstelasi Hukum Indonesia - Moch Isnaeni (Fakultas Hukum Universitas Islam Indonesia, 2000)
Although the Waqaf Board (Badan Waqaf) has accurately broken the modelof the distribution of wealth down, the need of societies, due to the acceleration of the development in this era, cannot be adapted to the available device model. Therefore, many parties presume that these material cases are necessary to be seriosly paid attention, especially on the distribution of the types of listed and unlisted wealth. The distribution is executed by maintaining the classification of movable and immovable objects, so the target of straightening the law of national wealth is attained.